Changes in Rohu (Labeo rohita) Actomyosin During Frozen Storage: Protein Denaturation or Coagulation? - Rao, Shrinivas B. (Fishery Technology, 2025)
Changes taking place in actomyosin extracted from Labeo rohita (Rohu) during storage at -20